Television viewing and abdominal obesity in women according to smoking status: results from a large cross-sectional population-based study in Brazil. - Cortes, T; Schlussel, M; Franco-Sena, AB; Rebelo, F; Kac, G (2013)
OBJECTIVE: To investigate the associations between television viewing and abdominal obesity (AO) in Brazilian women, according to smoking status. METHODS: Data of 13,262 adult women (18-49 years) from the 2006's Demographic Health Survey, a cross-sectional household study with complex probabilistic sample and national representativeness, were analyzed. AO, defined as waist circumference ≥ 80.0 cm, was the outcome. Television viewing frequency (≥ 5 times/week, 1-4 times/week, < 1 time/week) was the main exposure variable, and smoking status (yes or no) the main co-variable. Prevalence ratios were estimated using Poisson regression models separately for smokers and non-smokers. RESULTS: A statistically significant interaction term was observed between smoking status and television viewing (p < 0.05). Prevalence of AO among smokers who reported television viewing ≥ 5 times/week amounted to 59.0%, higher than the 35.0% for those with < 1 time/week television viewing (p-value = 0.020). The values for non-smokers were 55.2% and 55.7%, respectively. Smokers with television viewing ≥ 5 times/week were 1.7 times (95% CI: 1.1 - 2.5) more likely to pre-sent AO, compared to those who reported a frequency < 1 time/week. There was no significant association among non-smokers. CONCLUSIONS: Television viewing ≥ 5 times/week may increase the prevalence of AO among women who smoke. More detailed information on media use, as hours per day, may offer better estimates.